Genetic Diversity and DNA Barcoding Construction of Tropical Soybean Advanced Lines Based on SSR Markers - Kunto Wibisono; Rosliana Purwaning Dyah; Ratna Utari; Suparjo Suparjo; Umar Umar; Habib Rijzaani; Lukman Hakim; Ace Suhendar; Oky Dwi Purwanto; Dani Satyawan; Witjaksono Witjaksono; Mastur Mastur; Puji Lestari; I Made Tasma (Institut Pertanian Bogor, 2025)
Soybean cultivation in tropical regions, such as Indonesia, is often constrained by photoperiod sensitivity, resulting in low yield. Using long juvenile traits in short photoperiod tropical areas resulted in lines with late flowering time and high yield. Genetic diversity analysis of soybean lines using molecular markers is a critical step for breeding high-yielding soybean lines. This study aimed to analyze genetic diversity and construct DNA barcodes for 44 tropical soybean superior lines based on 17 SSR markers. Genetic materials used were the high-yielding F5 soybean lines developed for their adaptation to short day-length of low latitude tropical regions. SSR markers used were those that distributed well across the soybean genome and proven their usefulness for soybean genetic diversity analyses. Results showed that the SSR demonstrated distinctive polymorphism among the 44 lines. A total of 377 alleles were detected with an average of 22.8 alleles per SSR locus. Polymorphism information content (PIC) values varied from 0.77 to 0.96 with an average of 0.90. Phylogenetic analysis showed that the 44 soybean genotypes were divided into 2 main clusters. Five markers, i.e., satt009, satt646, satt147, satt431, and satt191, with a polymorphism information content value of ≥0.94, were found to be informative and suitable for DNA barcode construction. Each of the 44 lines was assigned with specific barcodes. The barcodes constructed from this study should be useful for DNA fingerprinting as well as protection purposes of the specific superior soybean lines analyzed in this study. Keywords: DNA fingerprint, molecular markers, photoperiod, plant breeding, soybean